Hubungan Dukungan Keluarga Sebagai Pengawas Minum Obat (PMO) Terhadap Keberhasilan Pengobatan TBC di Puskesmas Sawah Besar - Trianna, Nanda; Wahdini, Rizqa; Rosliany, Nia (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Tuberculosis (TB) remains a serious public health issue in Indonesia, which ranks second in the world for TB cases. One of the key factors in ensuring the success of TB treatment is patient adherence, which can be supported through the presence of a family member acting as a treatment supervisor, or Pengawas Minum Obat (PMO). This study aimed to determine the relationship between family support as PMO and the success of TB treatment in patients at Puskesmas Sawah Besar.This quantitative study used a cross-sectional design and descriptive analytic methods with a total sample of 39 respondents selected through total sampling. Data were collected using questionnaires and analyzed using univariate and bivariate analysis with Chi-Square tests. The results showed that most respondents received strong family support, and a significant number of them achieved successful treatment outcomes.The statistical analysis revealed a significant relationship between family support as PMO and the success of TB treatment (p < 0.05). The findings suggest that family involvement plays a vital role in supporting patients throughout their treatment, improving adherence, and increasing the likelihood of treatment success. Therefore, enhancing family education and engagement in TB programs is essential to reducing treatment failure and TB incidence.